Social Media Outrage in Response to a School-Based Substance Use Survey: Qualitative Analysis - Gassman, Ruth Ann; Dutta, Tapati; Agley, Jon; Jayawardene, Wasantha; Jun, Mikyoung (JMIR Publications, 2019)
BackgroundSchool-based alcohol, tobacco, and other drug use (ATOD) surveys are a common epidemiological means of understanding youth risk behaviors. They can be used to monitor national trends and provide data, in aggregate, to schools, communities, and states for the purposes of funding allocation, prevention programming, and other supportive infrastructure. However, such surveys sometimes are targeted by public criticism, and even legal action, often in response to a lack of perceived appropriateness. The ubiquity of social media has added the risk of potential online firestorms, or digital outrage events, to the hazards to be considered when administering such a survey. Little research has investigated the influence of online firestorms on public health survey administration, and no research has analyzed the content of such an occurrence. Analyzing this content will facilitate insights as to how practitioners can minimize the risk of generating outrage when conducting such surveys. ObjectiveThis study aimed to identify common themes within social media comments comprising an online firestorm that erupted in response to a school-based ATOD survey in order to inform risk-reduction strategies. MethodsData were collected by archiving all public comments made in response to a news study about a school-based ATOD survey that was featured on a common social networking platform. Using the general inductive approach and elements of thematic analysis, two researchers followed a multi-step protocol to clean, categorize, and consolidate data, generating codes for all 207 responses. ResultsIn total, 133 comments were coded as oppositional to the survey and 74 were coded as supportive. Among the former, comments tended to reflect government-related concerns, conspiratorial or irrational thinking, issues of parental autonomy and privacy, fear of child protective services or police, issues with survey mechanisms, and reasoned disagreement. Among the latter, responses showed that posters perceived the ability to prevent abuse and neglect and support holistic health, surmised that opponents were hiding something, expressed reasoned support, or made factual statements about the survey. Consistent with research on moral outrage and digital firestorms, few comments (<10%) contained factual information about the survey; nearly half of the comments, both supportive and oppositional, were coded in categories that presupposed misinformation. ConclusionsThe components of even a small online firestorm targeting a school-based ATOD survey are nuanced and complex. It is likely impossible to be fully insulated against the risk of outrage in response to this type of public health work; however, careful articulation of procedures, anticipating specific concerns, and two-way community-based interaction may reduce risk.